Infrastructure and logistics divide: regional comparisons between North Eastern & Southern Italy - Carlucci, Fabio; Cirà, Andrea; Forte, Ennio; Siviero, Lucio (Technological and Economic Development of Economy, 2017)
Only recently has the inequity among territories in terms of infrastructures and logistics services for freight transport become the subject of several studies regarding measurement and assessment of operational functionality and correspondence of supply for real mobility needs. The efficiency and competitiveness of territories are features that may be analysed through various parametric-type and non-parametric-type methodologies and with the construction of composite indicators. In reviewing recent literature, this article tackles the theme of measurement and assessment of the logistics and infrastructure divide with reference to the search for greater logistic efficiency and territorial competitiveness, in function of the specificities of local production systems and pursuable models of development in the global context. The purpose of this paper is twofold: to review the prevailing methods used to estimate regional efficiency and logistics competitiveness and to focus on an Italian case study. Focusing on the application of an original composite index to the Italian case study, the main insight of our analysis is that composite indicators could help policy-makers to evaluate the requirements of infrastructural interventions and logistics services, in close keeping with the characteristics of the local economic system. First published online: 09 Nov 2015